Effect of Compression Garments on the Development of Delayed-Onset Muscle Soreness: A Multimodal Approach Using Contrast-Enhanced Ultrasound and Acoustic Radiation Force Impulse Elastography - Heiß, Rafael; Kellermann, Marion; Swoboda, Bernd; Grim, Casper; Lutter, Christoph; May, Matthias; Wüst, Wolfgang; Uder, Michael; Nagel, Armin Michael; Hotfiel, Thilo (Journal of Orthopaedic & Sports Physical Therapy, 2018)
BACKGROUND: Delayed-onset muscle soreness (DOMS) is one of the most common reasons for impaired muscle performance in sports. However, little consensus exists regarding which treatments may be most effective, and the underlying mechanisms are poorly understood. OBJECTIVES: To investigate the influence of compression garments on the development of DOMS, focusing on changes in muscle perfusion and muscle stiffness. METHODS: In this controlled laboratory study with repeated measures, muscle perfusion and stiffness, calf circumference, muscle soreness, passive ankle dorsiflexion, and creatine kinase levels were assessed in participants before (baseline) a DOMS-inducing eccentric calf exercise intervention and 60 hours later (follow-up). After DOMS induction, a sports compression garment (18-21 mmHg) was worn on 1 randomly selected calf until follow-up, while the contralateral calf served as an internal control. Muscle perfusion was assessed using contrast-enhanced ultrasound (peak enhancement and wash-in area under the curve), while muscle stiffness was assessed using acoustic radiation force impulse (shear-wave velocities). A magnetic resonance imaging scan of both lower legs was also performed during the follow-up testing session to characterize the extent of exercise-induced muscle damage. Comparisons were made between limbs and over time. RESULTS: Shear-wave velocity values of the medial gastrocnemius showed a significant interaction between time and treatment (P = .006), with the noncompressed muscle demonstrating lower muscle stiffness values at follow-up compared to baseline or to the compressed muscle. No significant differences in soleus muscle stiffness were noted between limbs or over time, as was the case for muscle perfusion metrics (peak enhancement and wash-in area under the curve) for the medial gastrocnemius and soleus muscles. Further, compression had no significant effect on passive ankle dorsiflexion, muscle soreness, calf circumference, or injury severity, per magnetic resonance imaging. CONCLUSION: Continuous wearing of compression garments during the inflammation phase of DOMS may play an important role in regulating muscle stiffness; however, compression garments have no significant effects on intramuscular perfusion or other common clinical assessments. J Orthop Sports Phys Ther 2018;48(11):887-894. Epub12 Jun 2018. doi:10.2519/jospt.2018.8038.
EVALuna2:36098

Healing response of a structural hamstring injury: Perfusion imaging 8-week follow-up - Kellermann, Marion; Lutter, Christoph; Hotfiel, Thilo (Journal of Sport Rehabilitation, 2019)
Context: Hamstring injuries are frequently observed in various sports disciplines both in elite and recreational sport. Objective: To quantify intramuscular tissue perfusion via contrast-enhanced ultrasound in the acute phase and during the healing of a structural muscle injury confirmed by high-resolution magnetic resonance imaging. Design: Case study. Setting: Laboratory environment. Patient: A 32-year-old wakeboarder (height = 176 cm, body weight = 76 kg, and body mass index = 24.5 kg/m 2 ) with an acute indirect muscle injury of the semimembranosus muscle. Main Outcome Measures: Average values of quantifiable contrast-enhanced ultrasound, represented as peak enhancement and wash-in area under the curve, as well as conventional ultrasound, 1.5T magnetic resonance imaging were assessed at 48-hour, 3-week, and 8-week postinjury. Results: Average values of the quantitative perfusion analysis at 48-hour and 8-week postinjury revealed an approximate 5-fold increase in peak enhancement, and the wash-in area under the curve increased more than 3-fold in the center of the lesion. Magnetic resonance imaging, performed 48 hours after the injury to gather reference data as gold standard, revealed a grade III structural muscle tear. Conclusions: The authors are able to demonstrate significant changes in intramuscular tissue perfusion in the center of the structural lesion as well as in the adjacent tissue. Quantifiable contrast-enhanced ultrasound seems to be able to gather relevant data for the assessment and monitoring of muscle injuries and could be established as a valuable tool for further studies focusing on healing processes or therapeutic interventions.
CRIS-Team Scopus Importer:2020-02-21
Keywords: CEUS; MRI; Muscle healing; Muscle injury; Muscle regeneration